Blood red snow white - Sedgwick, Marcus (Square Fish, 2017)
Inspired by real-life children's book writer, Arthur Ransome, presents historical facts through a fictionalized plot. Leaving England, and an unhappy marriage, behind to work as a British correspondent in Russia during the Russian Revolution. However, he never expects to become the key piece in a game of espionage. Now suspected of being a double agent, Ransome would like nothing more than to flee and leave the turmoil behind him, but the Russian woman he's fallen in love with can't walk away so easily.